Differential Transcriptomics Analysis of IPEC-J2 Cells Single or Coinfected With Porcine Epidemic Diarrhea Virus and Transmissible Gastroenteritis Virus - Song, Lina; Chen, Jing; Hao, Pengfei; Jiang, Yuhang; Xu, Wang; Li, Letian; Chen, Si; Gao, Zihan; Jin, Ningyi; Ren, Linzhu; Li, Chang (Frontiers in Immunology, 2022)
Porcine epidemic diarrhea (PED) and transmissible gastroenteritis (TGE) caused by porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV) are two highly contagious intestinal diseases in the swine industry worldwide. Notably, coinfection of TGEV and PEDV is common in piglets with diarrhea-related diseases. In this study, intestinal porcine epithelial cells (IPEC-J2) were single or coinfected with PEDV and/or TGEV, followed by the comparison of differentially expressed genes (DEGs), especially interferon-stimulated genes (ISGs), between different groups via transcriptomics analysis and real-time qPCR. The antiviral activity of swine interferon-induced transmembrane protein 3 (sIFITM3) on PEDV and TGEV infection was also evaluated. The results showed that DEGs can be detected in the cells infected with PEDV, TGEV, and PEDV+TGEV at 12, 24, and 48 hpi, and the number of DEGs was the highest at 24 hpi. The DEGs are mainly annotated to the GO terms of protein binding, immune system process, organelle part, and intracellular organelle part. Furthermore, 90 ISGs were upregulated during PEDV or TGEV infection, 27 of which were associated with antiviral activity, including ISG15, OASL, IFITM1, and IFITM3. Furthermore, sIFITM3 can significantly inhibit PEDV and TGEV infection in porcine IPEC-J2 cells and/or monkey Vero cells. Besides, sIFITM3 can also inhibit vesicular stomatitis virus (VSV) replication in Vero cells. These results indicate that sIFITM3 has broad-spectrum antiviral activity.